1995
DOI: 10.1128/aac.39.1.200
|View full text |Cite
|
Sign up to set email alerts
|

Nikkomycin Z supersensitivity of an echinocandin-resistant mutant of Saccharomyces cerevisiae

Abstract: Echinocandins and nikkomycins are antibiotics that inhibit the synthesis of the essential cell wall polysaccharide polymers 1,3-␤-glucan and chitin, respectively. Some 40 echinocandin-resistant Saccharomyces cerevisiae mutants were isolated and assigned to five complementation groups. Four complementation groups contained mutants with 38 recessive mutations. The fifth complementation group comprised mutants with one dominant mutation, etg1-3 (strain MS10), and one semidominant mutation, etg1-4 (strain MS14).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 57 publications
2
41
1
Order By: Relevance
“…We have previously shown that FKS1 is likely to encode a subunit of 1,3-␤-D-glucan synthase (18). This conclusion was based primarily on the observation that certain mutations in FKS1 result in whole-cell resistance to the glucan synthase inhibitor L-733,560, a member of the echinocandin class of antifungal agents (45,72), as well as in glucan synthase activity which is resistant to L-733,560 in vitro (19,20). The high degree of similarity between Fks2p and Fks1p indicates that Fks2p is also likely to be a subunit of this enzyme.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that FKS1 is likely to encode a subunit of 1,3-␤-D-glucan synthase (18). This conclusion was based primarily on the observation that certain mutations in FKS1 result in whole-cell resistance to the glucan synthase inhibitor L-733,560, a member of the echinocandin class of antifungal agents (45,72), as well as in glucan synthase activity which is resistant to L-733,560 in vitro (19,20). The high degree of similarity between Fks2p and Fks1p indicates that Fks2p is also likely to be a subunit of this enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…1,3-␤-D-Glucan synthase (UDP-glucose:1,3-␤-D-glucan 3-␤-D-glucosyltransferase; EC 2.4.1.34) is a membrane enzyme activated by GTP which has been fractionated into soluble (GTP-binding) and membrane-bound (catalytic) components (39, 53). Members of the echinocandin family of antifungal agents inhibit 1,3-␤-D-glucan synthase and have been used to isolate mutations in the FKS1 gene, which encodes a subunit of this enzyme (18)(19)(20). The resistance mutations result in echinocandin-resistant enzyme activity which is associated with the membrane fraction (19).…”
mentioning
confidence: 99%
“…The link between FKS1 and the cell wall was established by the finding that ETG1 and PBR1 (whose mutants are resistant to ␤-1,3-GS inhibitors), CWH53 (required for resistance to calcofluor white), and CND1 (with mutant alleles requiring a functional calcineurin pathway) are all identical to FKS1 (44,76,80,91,231). FKS1 mutants show decreased ␤-1,3-GS activity, while Fks1 cofractionates with GS activity, implicating Fks1 as a ␤-1,3-GS catalytic subunit (76,119).…”
Section: ␤-13-glucanmentioning
confidence: 99%
“…The hyperaccumulation of chitin in response to cell wall stress is not limited to S. cerevisiae and is also found in other yeasts such as Kluyveromyces lactis (Uccelletti et al, 2000) and Candida albicans (Kapteyn et al, 2000). Inability of the cells to respond to cell wall damage by increasing chitin levels, either by disrupting the major chitin synthaseencoding gene (ScChs3p) or by adding the chitin synthase inhibitor nikkomycin Z, results in cell lysis, indicating the importance of the chitin response to prevent cell death (Douglas et al, 1994;el-Sherbeini & Clemas, 1995;Popolo et al, 1997).…”
Section: Introductionmentioning
confidence: 99%